Portal pseudo-hypertension. - Machado, Artur S (2006)
Authors present a case report of a 51 years old man, with a past history of peptic ulcer, arterial hypertension and dislipidemia. Three weeks before hospitalization he did a upper endoscopy that revealed a duodenal ulcer and oesophageal varices (grade II/III). During etiologic investigation, hepatic disease and portal hypertension were excluded. He had a goiter that invaded the anterior mediastinum. After thyroidectomy the oesophageal varices disappeared.